L'affaire - Johnson, Diane (Random House Audio, 2003)
Traveling to Europe to learn about her culture and find investment opportunities, successful dot-com executive Amy Hawkins becomes involved in an estate dispute involving the numerous children--many illegitimate--of an avalanche victim.